1985
DOI: 10.1128/aac.28.5.639
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, prospective, and double-blind trial of new beta-lactams in the treatment of appendicitis

Abstract: A prospective, randomized, and double-blind study was conducted with 864 patients operated on for appendicitis. In early cases, including normal and acute appendicitis, one dose of antibiotic was given. The rate of postappendectomy septic complications in patients who received cefotaxime, cefoperazone, or moxalactam was very low (about 3%), and there was no statistical difference between the drugs. For late cases, including gangrenous and perforated appendicitis, the antibiotics were continued for 5 days. Moxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
0
14
0
4
Order By: Relevance
“…Resistance to clindamycin was low, and it continues to be a very valuable drug in our armamentarium against these species. It is important to choose antimicrobial agents that are active against the pathogens involved in the infection (4,(6)(7)(8).…”
mentioning
confidence: 99%
“…Resistance to clindamycin was low, and it continues to be a very valuable drug in our armamentarium against these species. It is important to choose antimicrobial agents that are active against the pathogens involved in the infection (4,(6)(7)(8).…”
mentioning
confidence: 99%
“…In comparative clinical trials, poor results have been observed with cephaloridine [45,46], cefamandole [47,48], and cefoperazone [48,49]. In contrast, successful treatment of appendicitis and other intra-abdominal infections has been reported with cephalosporins that have good activity against anaerobic and aerobic/facultative bacteria, such as cefoxitin [50][51][52][53] and ceftizoxime [54,55].…”
Section: Cephalosporinsmentioning
confidence: 97%
“…Clinical correlates with these observations are not readily apparent in controlled trials. One possibly relevant report concerns the large study of appendicitis in which patients were randomized to receive cefoperazone, cefotaxime or moxalactam [11], In vitro studies and studies in our animal model show that of the three, only moxalactam has good activity against B. fragilis [2]. The results 358 Dezfulian/Bitar/Bartlett Efficacy of Ceftriaxone of the clinical trial showed no variation in out come among patients with uncomplicated ap pendicitis, whereas moxalactam was signifi cantly better in those who had late operations with gangrenous appendicitis, perforation or abscess formation.…”
Section: Discussionmentioning
confidence: 99%